Changes in linear and nonlinear measures of RR and QT interval series after beer intake - Platiša, Mirjana M; Gal, Vera; Nestorović, Zorica; Leskošek-Čukalović, Ida; Despotović, Saša; Veljović, Mile; Petrović, Aleksandar; Rajković, Jovana; Đokić, Vladimir; Novaković, Radmila; Gojković-Bukarica, Ljiljana (Vojnosanitetski pregled, 2018)
Background/Aim. There are only several studies on the acute effect of alcoholic drinks intake on heart rhythm and this phenomenon is still not well understood. We wanted to examine whether linear and nonlinear measures of RR interval and QT interval series could quantify the effect of beer in healthy subjects. Methods. Eighteen young volunteers drank 500 mL of beer (21 g of ethanol). Electrocardiogram (ECG) recordings were taken in supine position: 20 minutes before (relaxation) and 60 minutes after drink intake. The RR interval series and the QT interval series were extracted from ECG and we calculated short-term (α1) and long-term (α2) scaling exponents and sample entropy (SampEn) for both series; low frequency (LF) and high frequency (HF) spectral components from RR interval series and QT variability (QTV). Blood pressure was measured every 10 minutes. Results. It was shown that beer induced changes in variability and correlation properties of these series. Immediate effect of beer intake was detected as a transient increase in the QT variability, heart rate and blood pressure. Delayed effects of beer were shortening of the RR and QT intervals and reduction of the HF spectral component. Beer intake also increased short-term scaling exponent (α1) of the RR time series and long-term scaling exponent (α2) of the QT time series. Conclusion. Our results suggest that acute effects of beer are reduced parasympathetic control of the heart and changed dynamic complexity of the ventricular repolarization.
Keywords: alcohol drinking; beer; heart rate; electrocardiography; adult